2016
DOI: 10.1007/s00540-016-2253-7
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between successful intubation via the right nostril and anatomical variations of the nasopharynx during nasotracheal intubation: a multiplanar imaging study

Abstract: Successful intubation via the right nostril is related to the anatomy of structures on the posterior nasopharyngeal wall, particularly recesses located close to the path of nasotracheal tube insertion. Nasopharyngeal anatomical variations should be considered when one notices any resistance to advancement of the tube into the nasopharynx during nasotracheal intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…First, data have shown that less epistaxis occurred during NTI and intubation was faster in the right than in the left nostril, an effect related to the anatomy of structures located on the posterior nasopharyngeal wall; thus, the right nostril should be chosen if patency appears to be equal on both sides of the nose [1,11,12]. It was also reported that measurement of the nasal flow rate is a useful clinical method for choosing which nostril to use for NTI [13].…”
Section: Discussionmentioning
confidence: 99%
“…First, data have shown that less epistaxis occurred during NTI and intubation was faster in the right than in the left nostril, an effect related to the anatomy of structures located on the posterior nasopharyngeal wall; thus, the right nostril should be chosen if patency appears to be equal on both sides of the nose [1,11,12]. It was also reported that measurement of the nasal flow rate is a useful clinical method for choosing which nostril to use for NTI [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed many strategies to reduce the risk of epistaxis during NTI in clinical practice. First, data have shown that less epistaxis occurs during NTI and that intubation is faster in the right as opposed to the left nostril, which is related to the anatomy of the structures located on the posterior nasopharyngeal wall; thus, the right nostril should be selected if patency appears to be equal on both sides of the nose [1, 12, 13]. Measurement of the nasal flow rate has also been reported to be a useful clinical strategy for selecting which nostril to use for NTI [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed many strategies to reduce the risk of epistaxis during NTI in clinical practice. First, data have shown that less epistaxis occurred during NTI and intubation was faster in the right rather than the left nostril, which is related to the anatomy of the structures located on the posterior nasopharyngeal wall; thus, the right nostril should be selected if patency appears to be equal on both sides of the nose [1,12,13]. Measurement of the nasal flow rate has also been reported to be a useful clinical method for selecting which nostril to use for NTI [14].…”
Section: Discussionmentioning
confidence: 99%